Pharmacy and Therapeutics Committee in Bangalore Institute of Oncology - Promoting Rational Pharmaceutical Management - Hariharaputhran, Divya; C. Srinivas, Sunitha; S. Billimaga, Ramesh; Kumar B.S, Ajai (Indian Journal of Pharmacy Practice)
Bangalore Institute of Oncology (BIO), a Comprehensive Cancer Center operating since 1989 has initiated Pharmacy and Therapeutics Committee (PTC) in 2007 as a forward looking step in promoting rational use of medicines. The first step in establishing role of PTC was to carry out ABC Analysis of Anti-Cancer Drugs procured at BIO for the period of October 2006 to September 2007, according to Management Sciences for Health (MSH) and World Health Organization (WHO) guidelines. ABC Analysis provided a comprehensive and clear picture of consumption of chemotherapy medicines. The number of brand names procured for individual medicines were also collated. Constructive debate amongst PTC members resulted in making the decision to streamline the procurement of only three brand names for each medicine that had numerous brands procured earlier. PTC members of BIO have constructively utilized the forum in further improvising the pharmaceutical management as a first step in establishing PTC as a decision making body for rational use of medicines.
Keywords: Pharmacy and Therapeutics Committee; ABC analysis; Rational use of medicines